Efektivitas Pemberian Dukungan Sosial terhadap Self Esteem Orangtua yang memiliki Anak Autism Spectrum Disorder (ASD): Efektivitas Pemberian Dukungan Sosial terhadap Self Esteem Orangtua yang memiliki Anak Autism Spectrum Disorder (ASD) - Izzati, Nadia; Setiawati Hariyono, Dyta (Psikodinamika: Jurnal Literasi Psikologi, 2023)
Every couple wants offspring that are expected to be able to provide benefits, both for the family and the wider community. However, not all of the couple's wishes can be realized by having normal children, some are conferred to care for children with special needs, namely autism. Caring for autistic children certainly requires greater ability and patience, which also affects parents' self-esteem when caring for autistic children. This study aims to determine the effect of social support on the self-esteem of parents who have autistic children in the city of Banjarmasin. The subjects of this study were 70 parents who had autistic children. The sample data collection technique in this study used a saturated sample, and the data collection tool used a social support scale and a self-esteem scale. From the results of the data analysis carried out, there was a significant influence on social support (X) on self-esteem (Y). Keywords : Social Support, Self Esteem, Parents, Autism Spectrum Disorder.